PENTINGNYA REVISI PENGATURAN PERJANJIAN KERJA DI INDONESIA - Romi Romi (Masalah-Masalah Hukum, 2011)
The regulation of contract of employment system has produced some problems both in the sector labor and enterpreneur.lmplementation of this regulation is contrary with state philosophy and our consUtution.lt also has high potency to affect implementation of another rules which conduct related to Labor Social Guarantee. The problem is whether the regulation of contract employment system has the legal cerlainty, then how that regulation should be applied in the future. This research is based on normative approach and be analyzed on qualitative line. This research conclude that the regulations of contract employment system has not obtained the legal cerlainty yet. It opposed with Pancasila and Constitution. It also has affect the implementation of another rules related to labor social guarantee. That regulation,thus,has to be terminated due to opposed with Pancasila and Constitution